(The effect of nugmeg flesh (Myristica fragans)treatment on the quality of syrup) - Endah Djubaedah; Tiara -; Pudja Astuti (Warta Industri Hasil Pertanian, 1995)
The study is aimed at finding the optimum condition for nutmeg flesh soaking in salt solution before being proccesed into syrup. The nutmeg flesh used was fully ripe and 3/4 ripe, while the salt solution was 0%,5 % and 10%.The soaking was done for 0.3 and 6 days.The nutmeg syrup produced was stored for 0.3 and 6 week and the analysis was done for its sugar content,acidity,mould,yeast and organoleptic test. The analysis done on nutmeg flesh consisted of moisture,ash,fat,protein,and crude fiber content.The result showed that syrup made of nutmeg soaked in plain water or 5% salt solution did not show mould and yeast growth.During 6 week of storage the acidy increased and the sugar content decreased.The organoleptic test showed that highest score was obtained from syrup made of fully ripe or 3/4 ripe nutmeg flesh soaked in 5% salt solution.